Análise de ligação entre o substrato de concreto antigo e concreto auto adensável com lançamento subaquático - Mendes, Henry Silvério (2009)
The objective of this paper is to present the results of the connection between a substrate and self-compacting concrete with underwater launch simulating the repairs to concrete structures submerged in various applications. Therefore, we used samples of "old" concrete structures extracted from the Power Plant Itumbiara the state of Goiás, which was considered substrates. The concrete used in this work follows the parameters established strengths in the research completed in 2003 by the laboratory of Furnas Centrais Elétricas and has been adjusted to the materials (gravel and sand) found in the city of the Minas Gerais. The results are from the sample concrete of vertical and horizontal joints of the bodyspecimens prismatic concrete substrates and kept submerged and extracted after a year, so almost complete hydration. The analysis relating to the launch of concrete indicate that it is entirely feasible production for small applications. Visibility during the concreting was hampered by increased turbidity of the water produced by the concrete, so you must reduce the presence of a direct flow of water in concrete. The analysis was by comparing the results of the testimonies and bodies-of-proof. We observed an increase in strength in direct relation to the diameter of the testimony. In the samples concrete of 50 mm x 100 mm was obtained a coefficient of variation of 9.00% giving the concrete a low variability. The testimonies of concrete compounds and submerged concrete substrate (with seal inclined) had a resistance value 84% over the bodies-of-proof. The tensile strength by diametrical compression of the testimony amounted to 54% of the reference value. Can also check the interface between substrate concrete and after the break.